2008
DOI: 10.1017/s1138741600004480
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Functional and Dysfunctional Impulsivity and Aggression across Different Samples

Abstract: E. S. Barratt proposed the term impulsive aggression to define a kind of aggression that is characterized by acting without thinking because of high levels of impulsivity. Previous research using psychometric measures has shown that impulsivity and aggression are related as far as psychometric measures are concerned. Nevertheless, most of the research has been done with samples of university students. Our research tests whether this relationship is stable across different samples; university students, teenager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 38 publications
6
28
1
3
Order By: Relevance
“…As far as convergent validity is concerned, the I-DAQ scales showed the expected relationships with BPAQ and IAS, each scale showing the highest correlation with its analog scale of the tests used for validity. And as far as criterion validity is concerned, all the I-DAQ scales showed positive relationships with dysfunctional impulsivity, replicating the results previously found with other aggression measures (AnguianoCarrasco & Vigil-Colet, 2011;Vigil-Colet et al, 2008). With regard to the relationships between I-DAQ and personality dimensions, we found that AG and CO were related to physical aggression and the overall aggression score of I-DAQ.…”
Section: Discussionsupporting
confidence: 88%
“…As far as convergent validity is concerned, the I-DAQ scales showed the expected relationships with BPAQ and IAS, each scale showing the highest correlation with its analog scale of the tests used for validity. And as far as criterion validity is concerned, all the I-DAQ scales showed positive relationships with dysfunctional impulsivity, replicating the results previously found with other aggression measures (AnguianoCarrasco & Vigil-Colet, 2011;Vigil-Colet et al, 2008). With regard to the relationships between I-DAQ and personality dimensions, we found that AG and CO were related to physical aggression and the overall aggression score of I-DAQ.…”
Section: Discussionsupporting
confidence: 88%
“…In other studies, using BPAQ, this effect of the male gender was similar. (Abd-El-Fattah, 2013;Vigil-Colet et al, 2008;Condon et al, 2006;Prochazka & Agren, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…La impulsividad disfuncional se considera un marcador de vulnerabilidad para el desarrollo de trastornos adictivos (Paaver et al, 2006;Pedrero, 2009;Verdejo et al, 2008), juego patológico y otras adicciones conductuales (Maccalum et al, 2007;Meerkerk et al, 2010), así como conducta agresiva y antisocial (Strüber et al, 2008;Vigil-Colet et al, 2008). Nuestro trabajo permite afirmar que la dimensión de impulsividad disfuncional del modelo de Dickman también se muestra sensible al fenómeno del CIA, a diferencia de otros cuestionarios de impulsividad que no han consegui- …”
Section: Discussionunclassified
“…Ello es congruente con la constatación de que los hombres tienen menor autocontrol y un riesgo incrementado de sufrir alteraciones de los impulsos respecto a las mujeres (Maccallum, Blaszczynski, Ladouceur y Nover, 2007;Paaver et al, 2006;Strüber, Lück y Roth, 2008;Verdejo et al, 2008), siendo ello más evidente cuando se estudian jóvenes (Goodriaan et al, 2011;Perry y Carroll, 2008). Puntuaciones elevadas en impulsividad disfuncional se asocian a cogniciones desadaptativas (Mobini, Grant, Kass y Yeomans., 2007) y déficits en tareas de inhibición conductual y funciones ejecutivas (Vigil-Colet, 2007;Vigil-Colet et al, 2008). El DII se ha mostrado sensible a trastornos adictivos y del control de los impulsos (Meerkerk, van den Eijnden, Franken y Garretsen, 2010;Pedrero, 2009), hallándose puntuaciones de impulsividad disfuncional superiores en las muestras clínicas.…”
unclassified